Analysis of the influence of PTPN22 gene polymorphisms in systemic sclerosis. Issue 3 (3rd December 2010) - Diaz-Gallo, LM; Gourh, P; Broen, J; Simeon, C; Fonollosa, V; Ortego-Centeno, N; Agarwal, S; Vonk, MC; Coenen, M; Riemekasten, G; Hunzelmann, N; Hesselstrand, R; et al.
Abstract : Objective: Two functional single nucleotide polymorphisms (SNP) in the PTPN22 gene (rs24746601 and rs33996649) have been associated with autoimmunity. The aim of this study was to investigate the role of the R263Q SNP for the first time and to re-evaluate the role of the R620W SNP in the genetic predisposition to systemic sclerosis (SSc) susceptibility and clinical phenotypes. Methods: 3422 SSc patients (2020 with limited cutaneous SSc and 1208 with diffuse cutaneous SSc) and 3638 healthy controls of Caucasian ancestry from an initial case--control set of Spain and seven additional independent replication cohorts were included in our study. Both rs33996649 and rs2476601 PTPN22 polymorphisms were genotyped by TaqMan allelic discrimination assay. A meta-analysis was performed to test the overall effect of these PTPN22 polymorphisms in SSc. Results: The meta-analysis revealed evidence of association of the rs2476601 T allele with SSc susceptibility (pFDRcorrected =0.03 pooled, OR 1.15, 95% CI 1.03 to 1.28). In addition, the rs2476601 T allele was significantly associated with anticentromere-positive status (pFDRcorrected =0.02 pooled, OR 1.22, 95% CI 1.05 to 1.42). Although the rs33996649 A allele was significantly associated with SSc in the Spanish population (pFDRcorrected =0.04, OR 0.58, 95% CI 0.36 to 0.92), this association was not confirmed in the meta-analysis (p=0.36 pooled, OR 0.89, 95% CI 0.72 to 1.1). Conclusion: The study suggests that the PTPN22 R620W polymorphism influences SSc genetic susceptibility but the novel R263Q genetic variant does not. These data strengthen evidence that the R620W mutation is a common risk factor in autoimmune diseases.